Impact assessment of land use and land cover (LULC) changes on land surface temperature (LST) in Kuantan, Pahang - Ros Aniza, Mohd Nor (2016)
Pahang state has experienced a rapidly developed. The land use and land cover (LULC) is changed to accommodate the demand for many purposes such as residential, industrial, institutional and commercial purposes. The changes will make the increasing land surface temperature (LST) which contributes to the urban heat island (UHI) phenomenon. The coupling relationship between LULC changes and LST had been done on the previous study. The result obtained showed that the LST of different LULC use are differ significantly. The main objective of this study was to assess the impact of land use and land cover (LULC) changes on land surface temperature (LST) in Pahang state. This study uses the data satellite from public domain database to obtain the status of LULC and LST. Remote sensing and Geographical Information System (GIS) technique were used to detect the variation of LST based on LULC changes. The statistical analysis were performed to retrieve the relationship between LULC and LST. This study demonstrates the positive relationship between LULC changes and LST. The rapid development makes the LULC changes and makes the increasing LST.